The crystal growth in homopolymer polyvinylidene flouride (PVDF) and copolymer polyvinylidene flouride-triflouroethylene (PVDF-TrFE) / Dzuraiezhar Ismail - Ismail, Dzuraiezhar (2008)
Homopolymer PVDF (Polyvinylidene fluoride) and copolymer PVDF-TrFE (Polyvinylidene fluoride -Triflouroethylene) - exhibited ferroelectric properties due to the special arrangement of chain unit in crystalline phase. The samples were PVDF and different mol percentage of copolymer PVDF-TrFE (72-28), (65-35) and (51-49) dissolved in Dimethylformamide (DMF), Dimethyl sulfoxide (DMSO) and Tetrahydrofuran (THF) solvents. This work emphasize on crystal growth of PVDF and PVDF-TrFE. The crystalline structures were analyzed using Differential scanning calorimetry (DSC) and polarized light microscopy (PLOM). Samples were annealed to enhance crystal growth and observed using PLOM.